Optimization of EDGE terminal power amplifiers using memoryless digital predistortion - Ceylan, Nazim; Müller, Jan-Erik; Weigel, Robert (Radio Frequency Integrated Circuits Symposium, 2004)
This paper describes a look up table (LUT) based digital predistortion system usable for EDGE (enhanced data for GSM evolution) handset transmitters. The system is memoryless and capable of improving system efficiency and performance in terms of the leakage power at offset frequencies and error vector magnitude (EVM). Minimum system requirements on wordlength and LUT size have been investigated. It is shown that a LUT having about 500 coefficients and a system wordlength of 13 bits are sufficient for EDGE. The proposed system is simple and can be easily implemented in handsets in order to improve the overall system performance.
elib2cris::1512001600,ceylan2004a
Keywords: UHF power amplifiers; cellular radio; linearisation techniques; memoryless systems; mobile handsets; radio transmitters; table lookup; 13 bit; EDGE handset transmitters; EDGE terminal power amplifiers; EVM; LUT based digital predistortion; LUT size; enhanced data for GSM evolution; error vector magnitude; look up table wordlength; memoryless digital predistortion; offset frequencies leakage power; power amplifier linearization methods; power amplifier optimization; GSM; Linearity; Memoryless systems; Mobile communication; Power amplifiers; Power generation; Predistortion; System performance; Table lookup; Telephone sets